2011
DOI: 10.1080/00036846.2011.568405
|View full text |Cite
|
Sign up to set email alerts
|

Real wages, inflation and labour productivity in Australia

Abstract: This paper presents an analysis of real wages, inflation and labour productivity interrelationships using cointegration, Granger-causality and, most importantly, structural change tests. Applications of tests to Australian data over the period corroborate the presence of a structural break in 1985 and show that a 1 percent increase in manufacturing sector real wages led to an increase in manufacturing sector productivity of between 0.5 and 0.8 percent. Comparable estimates for the effect of inflation on manuf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 52 publications
(48 reference statements)
3
22
0
3
Order By: Relevance
“…They found that a 1% increase in real wages is correlated with a 0.6% increase in productivity for the panel as a whole. Similar results were obtained by Kumar et al (2012) who applied cointegration and structural tests to Australian data over the 1965 to 2007 period and got the result that a 1% increase in manufacturing sector real wages related to a 0.5% to 0.8% increase in manufacturing labour productivity. Srour et al (2006) performed statistical analyses to explore what the US construction industry values in its workers, as reflected in both hourly wages and average annual income.…”
Section: Wage Differentialssupporting
confidence: 81%
“…They found that a 1% increase in real wages is correlated with a 0.6% increase in productivity for the panel as a whole. Similar results were obtained by Kumar et al (2012) who applied cointegration and structural tests to Australian data over the 1965 to 2007 period and got the result that a 1% increase in manufacturing sector real wages related to a 0.5% to 0.8% increase in manufacturing labour productivity. Srour et al (2006) performed statistical analyses to explore what the US construction industry values in its workers, as reflected in both hourly wages and average annual income.…”
Section: Wage Differentialssupporting
confidence: 81%
“…7 See, for instance, Romer (1990) and Grossman and Helpman (1994) for details. 8 Some of the recent ones include Banerji and Dua (2004), Narayan andSmyth (2009), Kim, Lim, andPark (2013), Kumar, Webber, and Perry (2012) and Tang (2014). 9 See for instance, Fase and Abma (2003), Estrada, Park, and Ramayandi (2010), Bakaert et al (2009), Ang and Madsen (2013) and Timmer and Vries (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Some of the recent ones include Banerji and Dua (), Narayan and Smyth (), Kim, Lim, and Park (), Kumar, Webber, and Perry () and Tang ().…”
mentioning
confidence: 99%
“…The aim is to improve the knowledge of these variables due to their complexity and interrelation between them. According to Kumar et al (2012), the analysis of this mutual connection can provide policy directions for productivity improvement, inflation testing and consumption strengthening.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%